Convergence process in information sources: a view from press offices - González Molina, Sonia (Anàlisi, 2012)
Lately, convergence is in the middle of academic debates about journalism. However, there are a few researches from the point of view of the information sources, which are fundamental actors in the communication process. Bearing this in mind, this article trails convergence processes in this area from the experience of four press and communication offices on road information. It is organized through the four dimensions often used to explain convergence in media (integrated production, multiplatform delivery, multiskilling, active audience) in order to detect the main transformations unleashed by this phenomenon in communication areas. The changes documented on the media will be our reference. The methodology of this article combines quantitative (survey and documental analysis) and qualitative (deep interview and observation) techniques. This triangulation is usual in other researches about convergence. The fieldwork confirms the irruption of new ways to produce information and new platforms to distribute it among the journalists. Due to these changes, workers of press and communication offices assume more functions, so they become more polyvalent. But convergence does not create favorable conditions to a more virtual relation with journalists, who feel that these offices use digital technology to prevent a real dialogue.